2006
DOI: 10.1039/b603663e
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-catalysed bis-allylation of internal alkynes with triallylindium

Abstract: The Ni-catalysed reaction of triallylindium with internal alkynes underwent bis-allylation to afford octa-1,4,7-trienes in high yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…However, the addition of triallylindium reagent to internal alkynes proved to be difficult, and the reaction failed under palladium catalysis. Efforts made by Hirashita and co-workers revealed that the reaction progressed well in the presence of Ni(acac) 2 (1 equiv) and COD (2 equiv) to produce the bis-allylated product A predominantly (Scheme ) . However, under optimized conditions, the use of other allylmetallic reagents such as allylindium diiodide, allylindium sesquihalide, allylstannane, allylgallium, and allylmagnesium reagents led to poor efficiency.…”
Section: Triorganoindium Reagentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the addition of triallylindium reagent to internal alkynes proved to be difficult, and the reaction failed under palladium catalysis. Efforts made by Hirashita and co-workers revealed that the reaction progressed well in the presence of Ni(acac) 2 (1 equiv) and COD (2 equiv) to produce the bis-allylated product A predominantly (Scheme ) . However, under optimized conditions, the use of other allylmetallic reagents such as allylindium diiodide, allylindium sesquihalide, allylstannane, allylgallium, and allylmagnesium reagents led to poor efficiency.…”
Section: Triorganoindium Reagentmentioning
confidence: 99%
“…Organic chemists have noticed in many cases that organoindium reagents exhibited better performance than their organomagnesium and organozinc counterparts. Thus, the unique property of organoindium reagent also confers specific reactivity for carbon–carbon bond formations, allowing organic transformations to proceed with better selectivities (e.g., product yield and chemoselectivity). , …”
Section: Introductionmentioning
confidence: 99%
“… a 2.0 equiv of 2 and 10 equiv of HMPA were used unless otherwise noted. b The ratio was determined by 1 H NMR. c The absolute configurations of 3 , except for 3aE , were determined on the basis of the analogous reactions in Table (also see ref ). d The reaction was carried out at 0 °C. e The reaction was carried out at −20 °C. f The ee was determined by HPLC using the corresponding amino alcohol, which was prepared from 3kE by treatment of ozonolysis followed by reduction. g Using 3.0 equiv of 2E . h Using 5.0 equiv of 2M at 0 °C for 120 h. i The peaks of the 1,2- and 1,4-adducts overlapped in 1 H NMR. j Diphenylzinc was prepared by following literature k Diallylzinc was prepared by following literature …”
Section: Resultsmentioning
confidence: 99%
“…21 k Diallylzinc was prepared by following literature. 22 The Journal of Organic Chemistry corresponding 2-aminoalcohols. We demonstrated ozonolysis of 3aE with 98% ee, which was obtained by recrystallization, followed by reduction to afford the 2-aminoalcohol 14 in 89% yield without any loss of enantioselectivity (eq 2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Facile transmetalation involving allylmagnesium halide and indium trihalide generates reactive allylindium(III) intermediates in situ, with the latter being utilized in a followup allylation reaction. 172,191,211 For example, allylindiumdichloride 90A mediates the allylation of unprotected carbohydrates such as ribose 90a in aqueous ethanol, providing the corresponding allylated derivate 90b with high diastereoselectivity (Scheme 221). 172 Triallylindium(III), generated via magnesium-to-indium transmetalation, reacts with R,β-unsaturated nitrile and carbonyl compounds to give the corresponding 1,4-addition products (Scheme 222).…”
Section: Other Allylative Coupling Reactionsmentioning
confidence: 99%